The perceptions of trainee teachers on the integration of dramatic techniques to assess oral proficiency in school - based assessment / Muhammad Syafiruddin Mustafa - Mustafa, Muhammad Syafiruddin (Faculty of Education, 2014)
This study is carried out as to observe the integration of dramatic techniques to assess oral English proficiency in school - based assessment. As the traditional examination is being replaced by school - based assessment and innovation of policies being spread out in the Malaysian education field, it is crucial that teachers and students generally are to be allowed to develop physically, emotionally and mentally during their schooling years. Teachers specifically in direct relations to school - based assessment must be allowed autonomy over assessing their students through drama and dramatic techniques. Amidst the fast paced and ever - changing landscape of assessments in Malaysia, the teachers should have alternative methods other than the traditional ones of teaching and assessing oral English proficiency in an ESL classroom. This study investigated the perceptions of a group of trainee teachers, semester 8 graduate students, who had just finished their practicum sessions in schools within the Klang Valley, regarding the integration of dramatic techniques in assessing oral English proficiency in school - based assessment. It was found that the majority of the trainee teachers responded positively towards the integration of dramatic technique to assess oral English proficiency in school - based assessment. Hence, this study reveals the trainee teachers’ challenges and their students’ during the implementation of dramatic techniques to assess oral English proficiency in school - based assessment.